Migrant counterspaces: challenging labour market exclusion through collective action = Contre-espaces pour et par des migrant·e·s : lutter contre l’exclusion professionnelle par l’action collective - Mittmasser, Christina; Stingl, Isabella (Revue européenne des migrations internationales, 2021)
Recent debates in migration studies and labour geographies emphasise the need to acknowledge migrants’ agency and their ability to challenge regulatory migration regimes and precarious working relations. Contributing to this literature, this article examines the activities of a migrant-run organisation in Switzerland in its collective response to labour market barriers mobilised by the state, employers, and society at large. Building on ethnographic and participatory methods, our findings reveal that the organisation’s strategies focus strongly on the individual level and thus risk losing sight of broader power relations. Yet, our analysis also shows that the strategies employed can be transformative on the personal scale, creating a meaningful counterspace to dominant experiences of social and economic exclusion. In conclusion, we contend that an analysis of migratory movements needs to take into account the social and relational dimensions of agency as well as the differentiated effects of collective action.
Gesehen am 17.02.2025
Online veröffentlicht: 3. Januar 2023